An effective method to detect seam carving. (August 2017) - Ye, Jingyu; Shi, Yun-Qing
Abstract: Seam carving, also known as content-aware image resizing, is the most popular image resizing algorithm nowadays. Therefore, detecting seam carving has become an important topic in image forensics. In this paper, an advanced statistical model, consisting of local derivative pattern, Markov transition probabilities, and subtractive pixel adjacency model, is proposed to determine if an image has been seam carved or not. The performance of the proposed feature set can be further improved, and the feature set's dimensionality can be largely reduced by utilizing linear support vector machine (SVM) based recursive feature elimination. With the linear SVM classifier, the experimental works have demonstrated that the proposed approach can successfully detect seam carving. It outperforms the state-of-the-art in general; in particular at the low carving rate cases, such as 5%, 10% and 20%, the average detection accuracy has been boosted from 66%, 75% and 87% to 81%, 90% and 96%, respectively. On detecting seam carving in JPEG images and geometrical transformed uncompressed images, the proposed approach has also shown promising performance.